Freud and man's soul - "Bettelheim, Bruno" (London, 1982)
The English translations of Freud's writings are seriously defective in important respects and have led to erroneous conclusions, not only about Freud the man but also about psychoanalysis. This applies even to the authoritative Standard Edition of the Complete Psychological Works of Sigmund Freud. After reading the criticisms of this translation that I present in this book, the reader may well ask why I have waited so long to publish them, and why others have not waited so long to publish them, and why others have not made similar criticisms long ago.
Keywords: Psychology